ANALISIS TINGKAT INFLASI, KURS DAN TINGKAT BAGI HASIL SERTIFIKAT BANK INDONESIA SYARIAH (SBIS) SERTA DAMPAKNYA TERHADAP INVESTASI ASING DI INDONESIA - Arisman, - (2019)
Foreign investment is one of the sectors that able to contribute positively in realizing economic development in Indonesia. In addition, foreign investment can also be used by the government as an alternative solution in reducing the government's dependence on foreign loans to cover the budget deficit in the state income and expenditure (APBN). However, the entry of foreign investment into the country in the last period has decreased while experiencing an upward trend in several previous periods. This research aims to analyze the effect of macroeconomic variables reflected through the inflation rate, IDR-USD exchange rate and profit sharing rate of Bank Indonesia Sharia Certificate (SBIS) on foreign investment in Indonesia using the Vector Error Correction Model (VECM) methodology. The data used ist secondary data as much as 96 periods from January 2011 to December 2018. The results showed that all variables in the short run doesn't have a significant effect on foreign investment. Whereas in the long run the variable inflation rate and IDR-USD exchange rate have a significant negative effect and the profit sharing rate of SBIS variable has a significant positive effect. Then based on the results of the Impluse Response Function (IRF) test, it shows that foreign investment in Indonesia reaches the fastest stability when dealing with profit sharing rate of SBIS shock compared to other variables. While based on the results of the Forecasting Error Variance Decomposition (FEVD) analysis, it can be concluded that the variable giving the biggest contribution until the end of the period to foreign investment is foreign investment itself.